On the accuracy of CORDEX RCMs to project future winds over the Iberian Peninsula and surrounding ocean. (15th October 2018) - Santos, F.; Gómez-Gesteira, M.; deCastro, M.; Añel, J.A.; Carvalho, D.; Costoya, Xurxo; Dias, J.M.
Highlights: The skill of CORDEX models to reproduce wind over the Iberian Peninsula. CORDEX RCMs showed a higher skill than CMIP5 GCMs to reproduce in-situ data. CORDEX wind speed was projected for the 21st century showing an overall decrease. Wind increase is only projected at some isolated locations. Abstract: The accuracy of CORDEX regional models to reproduce wind speed was assessed at 15 wind farms (216 wind turbines) and 13 oceanic buoys covering the Iberian Peninsula and surrounding ocean during 2012. Models were able to reproduce with relative accuracy both the mean wind speed, with a mean error of 19% inland and 10% offshore, and the wind distribution, with an overlap percentage between distributions of 82 ± 5% inland and 83 ± 3% offshore. In addition, CORDEX regional models showed a skill higher than CMIP5 general models. Wind speed and wind power were projected over the Iberian Peninsula (Spain and Portugal) and the surrounding ocean for three future periods: near future (2019–2045), midterm (2046–2072) and far future (2073–2099) both at annual and seasonal scales. Both wind speed and wind power will decrease over most of the area with the exception of some regions as: Galicia; the Atlantic coast of Galicia and north of Portugal; the Ebro Valley; the upper Douro Valley; the Guadalquivir Valley; the Strait of Gibraltar and Cape Gata where both will tend to increase. This increase is projected to occur mostly during summer except at the Strait of Gibraltar where it will occur all year long. The change in wind speed and power is higher as farthest the future period is.